Examining the factors influencing adoption of e-banking services in Chennai city - N, Akbar Jan; A K, Subramani; Chebolu, Radha Mohan; M S, Sasikala (Serbian Journal of Management, 2020)
India being a developing country still has millions of people who prefers to have traditional branch banking system rather than e-banking. The reason behind their preference is either they hesitate or they don’t have sufficient knowledge about the e-banking services. The purpose of this study is to examine the relationship between perceived usefulness, perceived barriers, customer attitude, and perceived effectiveness of adoption of e-banking services. An effective number of responses of 470 respondents from both public and private banks’ customers were used to examine the hypothesized relationships. Structural equation modelling are performed to test the constructs and their relationships. The study found that there is a direct relationship between perceived usefulness and technology adoption in developing customer attitude toward adoption of e-banking services; whereas, there is no relationship between perceived barriers and technology adoption. The sample size and potential respondents from a selected region of the study may limit its wider applicability and generalization.